Marriage During the Wife’s ‘Iddah Period: A Socio-Legal Analysis of the Implementation of Circular Letter No. 05 of 2021 in Solok Regency - Darmis, Jhon; Zulkifli, Zulkifli; Yunarti, Sri; Maulana, Ramza Fatria (Civiliza Publishing, 2025)
This study examines marriage during a wife’s iddah period from the perspective of Islamic family law by analyzing Circular Letter of the Director General of Islamic Community Guidance No. 05 of 2021 and its implementation in Solok Regency. The research addresses a normative gap in Indonesian positive law, which does not explicitly regulate restrictions on ex-husbands remarrying during the ex-wife’s iddah, potentially leading to legal uncertainty, gender inequality, and weak protection for women after divorce. Using a qualitative socio-legal approach, data were collected through in-depth interviews, observation, and documentation involving KUA officials, religious counselors, and community leaders. The findings indicate that the circular letter functions as an administrative policy (beleidsregel) that guides KUA in controlling marriage registration and preventing harmful practices such as serial marriages and disguised polygamy. However, its implementation varies between strict and adaptive approaches, influenced by bureaucratic discretion, local socio-cultural contexts, and uneven legal literacy. While KUA officials generally show consistent understanding, religious counselors and community leaders demonstrate diverse interpretations due to limited policy dissemination and persistent conventional fiqh perspectives. From the maqāṣid al-syarī‘ah perspective, the policy supports the protection of lineage, dignity, and psychological well-being, while promoting gender justice. The study concludes that the circular letter represents institutional ijtihad, though its effectiveness depends on consistent implementation and strengthened legal communication.